Армада: маленький роман / Илья Бояшов - Бояшов Илья Владимирович (Амфора, 2007)
Экземпляры: ф16 (20250324) / Инвентарный номер: 43729 / Цена: 262.02 / Сис.шифр: Р2 / Авт.знак: Б 86 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6